Adsorption and Electrochemical Detection of Bovine Serum Albumin Imprinted Calcium Alginate Hydrogel Membrane - Qi, Meng (Polymers (Basel), 2019)
In this paper, bovine serum albumin (BSA)-imprinted calcium alginate (CaAlg) hydrogel membrane was prepared using BSA as a template, sodium alginate (NaAlg) as a functional monomer, and CaCl(2) as a cross-linker. The thickness of the CaAlg membrane was controlled by a glass rod enlaced with brass wires (the diameter was 0.1, 0.2, 0.3, 0.4, and 0.5 mm). The swelling properties of the CaAlg membranes prepared with different contents of NaAlg were researched. Circular dichroism indicated that the conformation of BSA did not change during the preparing and eluting process. The thinner the CaAlg hydrogel membrane was, the larger the adsorption capacity and the higher the imprinting efficiency of the CaAlg. The maximum adsorption capacity of molecularly imprinted polymer (MIP) and non-imprinted CaAlg hydrogel membrane (NIP) was 38.6 mg·g(−1) and 9.2 mg·g(−1), respectively, with an imprinting efficiency of 4.2. The MIP was loaded on the electrode to monitor the selective adsorption of BSA by voltammetry curve.